Global Oil-Price Slump Crisis - The impacts to PTSC M&C’s planning and production and its Implication - Đong, Đai Nghia (H. : ĐHQGHN, 2020)
The study has examined both external situations and internal factors of PTSC M&c to come to a conclusion. The falling oil prices is the most critical factor driving down PTSC M&C’s business at the moment. In the near future, it is expected to continue to negatively affect the company.